Agriculture and nutrition in Bangladesh: Mapping evidence to pathways - Yosef, Sivan; Jones, Andrew D.; Chakraborty, Barnali; Gillespie, Stuart (SAGE Publications, 2015)
Background: Although much work has been done on the theoretical links between agriculture and nutrition, there is limited understanding of the evidence from observational and experimental research studies on the impacts of agriculture programs on nutrition outcomes.